PENERAPAN KONSEP SYIRKAH-MUDHARABAH DALAM KEGIATAN EKONOMI MASYARAKAT DI TASIKMALAYA - Suryanto, Asep (LIPI, 2016)
Basically, business cooperation in Islam is in order to help each other between pihakyang have the business skills to the owners of capital, either individually or institutionally. This is done in binbgkai to make ends meet. The purpose of this research is to investigate the application of Musharaka contract-muhdarabah in economic activities, application know-muhdarabah contract Musharaka Islamic financial institutions in Tasikmalaya. The method used in this research is descriptive method with qualitative analysis. Sources of data in this research is secondary data, ie data derived from source documents and writings are closely related to the discussion of the study, both in the form of books, articles, and others related to the discussion of the author. His research results show that 1) the application of the concept of Musharaka-mudharabah have done and are well known by the public in the context of economic activities and a thriving business community with the aim to help each other mutually beneficial business activity and berkeadilan.2) penerapankonsep musyarakah-mudharabah institutions Islamic finance is done in the form of grant funding and financing schemes using musharaka-mudharabah contract based on a fatwa of the National Sharia god.